The Determinants of Sell-side Analysts’ Forecast Accuracy and Media Exposure - Samira Amadu Sorogho (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study examines contributing factors to the differential forecasting abilities of sell-side analysts and the relation between the sentiments of these analysts and their media exposure. In particular, I investigate whether the level of optimism expressed in sell-side analysts’ reports of fifteen constituents of primarily the S&P 500 Oil and Gas Industry1, enhance the media appearance of these analysts. Using a number of variables estimated from the I/B/E/S Detail history database, 15,455 analyst reports collected from Thompson Reuters Investext and analyst media appearances obtained from Dow Jones Factiva from 1999 to 2014, I run a multiple linear regression to determine the effect of independent variables on dependent variables.  I find that an analyst’s forecast accuracy (as measured by the errors inherent in his forecasts) is negatively associated with the analyst’s level of media exposure, experience, brokerage size, the number of times he revises his forecasts in a year and the number of companies followed by the analyst, and positively associated with the analyst’s level of optimism expressed in his reports, forecast horizon and the size of the company he follows.